Natural Variation for Seed Physical, Biochemical and Culinary traits in Common bean (Phaseolus vulgaris L.) - Saba,, Iram; A. Sofi,, Parvaze; U. K., Kandoliya*; Z.A, Baba (Current Botany, 2015)
Twenty genotypes of common bean including 17 breeding lines were evaluated for various seed physical, nutritional and culinary traits viz., seed colour, seed shape, seed brilliance, seed coat pattern, seed length, seed breadth and seed weight, traits protein content, phytic acid, raffinose, water absorption percentage, coat percentage, swelling and hydration coefficient as well as cooking score. Most of the genotypes were kidney shaped with plain seed coat and medium seed brilliance. Among biochemical traits, highest protein content was recorded for Arka Anoop (22.15 %) followed by WB-341 (21.45 %), WB-216 (21.16 %) and WB-249 (20.99). Low phytic acid was recorded in WB-970 (0.440 %), WB-258 (0.968 %) and WB-102 (1.068 %). Low values for raffinose was recorded for WB-102 (3.800 mg/g) followed by WB-482 (3.833 mg/g). Highest water absorption percentage was recorded for WB-249 (136.363), Arka Anoop (131.818) and SFB-1 (126.923). The swelling coefficient was highest in case of WB-642 (300.000), WB-249 (266.667) and WB-335 (250.000) whereas lowest values for swelling coefficient were recorded in case of WB-341 (114.285), WB-216 (145.454) and WB-1006 (124.554). Among correlations between various seed physical, biochemical and culinary traits, raffinose was positively and significantly correlated with phytic acid. Phytic acid was also significantly and positively correlated with protein, coat proportion and 100-seed weight. Coat proportion was negatively correlated water absorption percentage, swelling coefficient, hydration coefficient as well as cooking time score. Cooking time score was positively correlated with hydration and swelling coefficients as well as seed weight but negatively correlated with coat proportion.